Islamic Communications Management Communications And Informatics Office In Making Dignified North Sumatra - Mhd Fitriyus; Ahmad Tamrin Sikumbang; Elfi Yanti Ritonga (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The research aims to analyze communication and public information planning by Islamic communication principles to create a dignified North Sumatra. How the Communication and Informatics Department organizes the implementation of public communication and information so that it reaches the community to create a dignified North Sumatra. The research approach used is qualitative with descriptive methods. Informants were selected purposively as many as 8 people. Data was collected through observation, interviews, and document study. Next, analyze the data using the Miles and Huberman version of the data analysis technique, the steps are: collecting, reducing, displaying, and drawing conclusions and verification. Research results: first, there are Islamic communication principles that are applied in the planning and implementation of communication and public information at the North Sumatra Diskominfo, namely qawlan laying, qawlan sadīdan, and qawlan balīghan. Second, the method of organizing public communication and information implementers by the North Sumatra Diskominfo is based on the Governor's Regulation, 09/2023 concerning the Composition of OPD and the Governor's Regulation, 28/2023 concerning Tusi, Job Descriptions and Work Procedures for Provincial Regional Apparatus. From this regulation, efforts for synergy and cooperation with the media crew and related stakeholders were developed, including acting as the leading sector and Chair of Bakohumas. Third, there are at least 8 ways to carry out communication and disseminate information to the public in line with the values of Islamic Communication principles/ethics, namely honesty; saying positively; including heart, words, and deeds; supervision; election; interplay; and balance. Fourth, efforts to overcome obstacles are carried out by building and developing partnerships, synergy and collaboration with related parties, the media and other stakeholders. Even though the program can be implemented, it is necessary to strengthen and train human resources and provide priority facilities so that the vision of Dignified North Sumatra can be realized optimally.